Helicobacter pylori antibiotic susceptibility patterns in Bangladesh: Emerging levofloxacin resistance - Hafeza Aftab; Muhammad Miftahussurur; Phawinee Subsomwong; Faruque Ahmed; AK Azad Khan; Yoshio Yamaoka (Journal of Infection in Developing Countries)
Introduction: The most recent study to report Helicobacter pylori antibiotic resistance rates in Bangladesh was published 15 years ago and did not include levofloxacin. We therefore aimed to determine the current antibiotic susceptibility of H. pylori to amoxicillin, clarithromycin, metronidazole, tetracycline and levofloxacin in Bangladesh. Methodology: This study included 133 consecutive patients who underwent endoscopy examination at Dhaka Medical College in November 2014. The serial two-fold agar dilution method was used to determine the minimum inhibitory concentrations of the five antibiotics. Results: Among 56 cultured strains, H. pylori showed high rates of resistance to clarithromycin and metronidazole (39.3% and 94.6%, respectively). Moreover, levofloxacin showed an emerging antimicrobial resistance pattern (66.1%), which was higher in patients with gastritis than that in those with peptic ulcers (p = 0.02). The resistance rate of levofloxacin was significantly higher in patients living in Dhaka city compared to those living in the village (p = 0.049). However, amoxicillin and tetracycline resistance rates were very low. Resistance to both metronidazole and levofloxacin was most commonly observed. Conclusions: The rates of resistance to clarithromycin, metronidazole, and levofloxacin were high in Bangladesh, which suggests that triple therapy based on these drugs may not be useful as first-line therapies in Bangladesh. Alternative strategies such as furazolidone-based triple therapy, bismuth-based quadruple therapies, or sequential therapy may be more effective for patients in in Bangladesh.